Paclitaxel Restores Sensitivity to Chemotherapy in Preclinical Models of Multidrug-Resistant Intrahepatic Cholangiocarcinoma - Massa, Annamaria; Peraldo-Neia, Caterina; Vita, Francesca; Varamo, Chiara; Basiricò, Marco; Raggi, Chiara; Bernabei, Paola; Erriquez, Jessica; Sarotto, Ivana; Leone, Francesco; Marchiò, Serena; Cavalloni, Giuliana; et al. (Frontiers in Oncology, 2022)
The treatment of unresectable cholangiocarcinoma (CCA) is limited by the development of resistance to conventional first-line chemotherapy based on Gemcitabine (GEM). In addition, a prior treatment with GEM frequently induces cross-resistance to other drugs employed in second line. Paclitaxel (PTX) is now emerging as an alternative option for the management of advanced/metastatic CCA. In the present work, we evaluate the antitumor activity of PTX in preclinical models of multidrug-resistant intrahepatic cholangiocarcinoma (iCCA). In vitro, PTX decreases tumor cell viability by affecting the cell cycle and inducing apoptosis, and impairs the stem cell compartment. In vivo, a therapeutic regimen containing albumin-bound nanoparticle (Nab)-PTX overcomes drug resistance resulting in delayed tumor growth, impaired organization of the tumor vasculature, and reduced glucose uptake. Together, our results provide a rationale to consider PTX-based regimens in patients with iCCA who became refractory to conventional therapies.